The role of communicative situations in improvement of students’ foreign language speaking skills - Kopzhasarova, U.I.; Sarvanidi, Y.A.; Makhatova, A.K (KSU Publ., 2018)
The article is devoted to the problem of using speech communicative situations for improvement of students' communicative skills at a foreign language lesson. The analysis of scientific and theoretical literature on the problem under research was carried out. The article touches upon the issues of speech formation in the framework of speech situations. Detailed and thorough classifications of speech situations are considered and one of the most effective ways of teaching oral speech identified; on the basis of which, the authors emphasize significant role of speech situations in enhancement of high-school students' communicative ability. The authors conclude that mostly problem-solving situations play an important role in communicative skills improvement, because they create good opportunities for the development of students' thinking and analytical skills. The specific features of development of problem-solving situations at foreign language lessons are demonstrated. Different activities on the use of communicative situations at high- school classes are given in the article.
Студенттердің шетел тіліндегі сөйлеу білігін дамытудағы қарым-қатынас жағдаяттарының рөлі
Роль коммуникативных ситуаций в совершенствовании иноязычной устной речи учащихся
Keywords: foreign language; communicative situation; communicative competence; speech situations; threephase structure of activity; speech exercises; real situations; conditional situations; problem solving situations; thinking skills; motivation; self-awareness; independent work